Selected Factors related with the Health Literacy of Village Health Volunteer - เตชะวิจิตรจารุ ชินตา; ศรีสุภรกรกุล อัจฉรา; ช้างเทศ สุทัตตา (Journal of The Royal Thai Army Nurses, 2018)
The purposes of this analytic cross-sectional research were to study the level and the selected factors related with the Health Literacy of Village Health Volunteer in Mueang District Nakornpathom Province. The samples were 342 Village Health Volunteers (VHS.) selected by using Stratified random sampling. The research tool was ABCDE-Health Literacy questionnaire of Health Education Division, Ministry of Public Health, consisted of 2 parts 1) The selected factors composed of: gender, age, educational level, occupation and marital status 2) The questionnaire of health knowledge and understanding in health. The reliability was KR 20 at 0.64. and the questionnaire of health information and services, health communication, self-management, media literacy and the decision to right practice was yielded of Cronbach’s alpha coefficient at 0.78. Data was analyzed by descriptive statistics and chi-square. The study revealed that VHS’s ABCDE-Health literacy and 5 skills of Health Literacy level were fair excluding the decision to right practice that was very good. Gender, age, education, occupation and marital status factors had no relationship with ABCDE-Health Literacy. For each dimension analysis, gender related with health knowledge and understanding in health including education related with media literacy was shown significantly .Occupation was significantly related with self-management as well. The suggestion was to provide budget supported by Provincial Health Office to develop the program enhancing the level of Health Literacy on 6 skills especially skill 1-5.